Oppvekst og livstolkning Flerfaglige blikk på barns og unges eksistens, fellesskap og fortellinger - Hugaas, Jon Vegard; Kallestad, Åse Høyvoll (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
What is the meaning of friendship? Can the meaning of life be found in football fan culture? What do pupils learn about the environment in ethics classes in schools and what does a young refugee girl think about God? This are but some of the questions raised in this anthology where scholars from a variety of fields within teacher education examine existential and moral life questions from child and youth perspectives in various cultural expressions such as TV-series, fiction literature and real life encounters. The anthology examines how curricula and textbooks relate to the challenges of diversity and the urgent call for sustainability, and raise questions concerning the implementation of overreaching principles of democracy and citizenship in school. By approaching moral and existential questions of life from a child and youth perspective, this book offers a valuable contribution to the professional discourse within teacher education.